Dr. Edwin Wright Collection: Jessica B. Watson (nee Segers) - (Author); (Interviewer); (Publisher) (1961)
Notes - Mrs. Jessica B. Watson writes about her family life in Athabasca. Her father, Captain F. S. Segers, worked for the Hudson's Bay Company and was "in charge of all of the boat transportation up and down the river." Mrs. Watson speaks of travelling, pets, entertainment, and daily life in Athabasca, where she arrived ,via stagecoach and buckboard, when she was 16 years old, in 1891 (1 page)